The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0891243217742110
|View full text |Cite
|
Sign up to set email alerts
|

Gender Conformity, Perceptions of Shared Power, and Marital Quality in Same- and Different-Sex Marriages

Abstract: Research on gender inequality within different-sex marriages shows that women do more unpaid labor than men, and that the perception of inequality influences perceptions of marital quality. Yet research on same-sex couples suggests the importance of considering how gender is relational. Past studies show that same-sex partners share unpaid labor more equally and perceive greater equity than do different-sex partners, and that lesbian, gay, and bisexual people are less gender conforming than heterosexuals. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Research by Hatzenbuehler (2009) suggests that this may occur because respondents with more discriminatory experiences respond with rumination and suppression, limiting their opportunity to receive support. Thus, differences in spousal support are more likely to be a reflection of how dominant notions of gender may impose pressures that shape marital dynamics (e.g., Pollitt, Robinson, and Umberson 2018). Overall, findings point to the importance of considering differences by both respondent and spouse gender.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Hatzenbuehler (2009) suggests that this may occur because respondents with more discriminatory experiences respond with rumination and suppression, limiting their opportunity to receive support. Thus, differences in spousal support are more likely to be a reflection of how dominant notions of gender may impose pressures that shape marital dynamics (e.g., Pollitt, Robinson, and Umberson 2018). Overall, findings point to the importance of considering differences by both respondent and spouse gender.…”
Section: Discussionmentioning
confidence: 99%
“…Daily‐diary methods involve the collection of data, typically via short daily questionnaires, over a period of days or weeks (Bolger & Laurenceau, ). This approach is ideal for examining relationship dynamics that unfold over short periods of time (e.g., the effect of daily stress levels on relationship conflict) and has been used to examine gender differences in relationship experiences and consequences (Pollitt, Robinson, & Umberson, ). Finally, longitudinal multiyear data sets are rare in studies of SGM‐member couples, but they have been paramount in studies of different‐sex cisgender‐member couples in order to understand how gender dynamics unfold over time within aging romantic relationships as well as the gendered consequences of relationship dissolution.…”
Section: Gar‐driven Methodsmentioning
confidence: 99%
“…Yet research within a GAR approach allows us to examine relationship dynamics in multiple contexts, comparing couples with two men or two women and testing whether his and hers marriages might extend to these contexts. These studies show that there are gender differences when comparing relationships between two men and two women in the determinants of relationship quality (Cooper et al, ; Pollitt, Robinson, & Umberson, ). For example, Pollitt et al (), in their study of midlife couples, found that greater gender conformity is associated with more shared power and with greater marital quality in same‐sex men couples and different‐sex couples, but not in same‐sex women couples.…”
Section: Applying a Gar Framework In Research On Aging Romantic Relatmentioning
confidence: 99%
See 1 more Smart Citation
“…For families with dual parents, childcare and household tasks may be more collaborative than before the pandemic, which may also improve wellbeing. Having a family is associated with an increased sense of purpose and responsibility for parents which has positive impacts on mental and physical health (Pollitt, Robinson, & Umberson, 2018). These effects may be enhanced during the pandemic as a result of increased time spent with children and the need to provide support and a sense of normalcy for children during a highly stressful time.…”
Section: Discussionmentioning
confidence: 99%